Shiva Linga in the Garbhagriha of the Sheshashayi Vishnu Temple - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) has a pedestal with a Shiva linga currently placed on it. Originally, the temple housed an image of Sheshashayi Vishnu, which is now placed in the Kota Museum.